An Urban Architecture Study of the Residential Environment in Juppandang Subdistrict, Enrekang City - Izharul Haq; Nurhayati Kamaruddin (Journal Of Architectural Design & Technology, 2025)
Juppandang Subdistrict is one of the residential areas in Enrekang City that has experienced physical and social development along with urban growth. This development has affected changes in spatial patterns, building characteristics, and the quality of the residential environment. This study aims to examine the condition of the residential environment in Juppandang Subdistrict from an urban architecture perspective, focusing on spatial structure, settlement patterns, physical characteristics of buildings, and the relationship between space and community activities. The research employs a descriptive approach, with data collected through field observations, documentation, and interviews with local residents. The results indicate that the residential environment in Juppandang Subdistrict has developed organically, influenced by the social, economic, and cultural conditions of the community. The resulting settlement pattern tends to be unplanned as a whole, leading to limitations in open space, circulation, and overall environmental quality. This study is expected to serve as a reference for more sustainable and urban-architecture-oriented planning and management of residential environments in Enrekang City.